RESTRUCTURING of SYSTEMS and LOGISTICS of MOVEMENT and ITS IMPACT on URBAN and REGIONAL PLANNING PAULISTA - Silveira, Rogerio Marcio [UNESP] (Univ Barcelona, Dept Geografia Humana, 2010)
Report some of the changes in production and consumption occurring in the state of São Paulo. through the restructuring in motion systems, logistics and standards and taxation, as well as the impacts on urban spaces through new economic dynamics, imposed by the demands of corporate, is the purpose of this article. The decentralization of production and consumption towards the interior was made possible by the combination of hierarchical and ordered some basic elements such as technological innovations (ways and means of transport) and organizational (logistics, standards and taxation) which optimized the flow territorial state São Paulo. It is noteworthy, therefore: 1) the improvement of logistics as a strategy, planning and management of transport, storage and communications (including the granting of public services to private), 2) the technological improvement and expansion of motion systems (infrastructure, means of transport) and 3) the systems of rules and regulations through taxation and deregulation affect the circulatory system of a given space. Thus, both systems aims to disentangle the economic flows (goods, services, information, capital and people) and provide a more fluid territorial. The impacts on the State of São Paulo, mainly through its economic dynamics, revert positively and negatively, by changing the way one thinks and performs planning.
Keywords: logistics; territorial fluidity; motion systems; flows and economic dynamics